The Effect of Credit Risk, Liquidity Risk, and Bank Capital on Bank Profitability During the COVID-19 - Jessica Lilia Chandra; Elizabeth Lucky Maretha (Soegijapranata Catholic University, 2024)
This research aims to examine the impact of credit risk, liquidity risk, and bank capital on profitability banks in Indonesia and Malaysia during the global economic crisis of Covid-19 using panel regression analysis methods by E-views software. The research sample was 232 observational data for Indonesian banking and 64 observational data for Malaysian banking that were gained with purposive sampling method from 2020-2021 quarterly. The results of this study: are credit risk has a significant and negative impact on the profitability of Indonesian banks but has no effect on the profitability of Malaysian banks; liquidity risk has a significant and positive impact on the profitability of Indonesian banks but has no effect on the profitability of Malaysian banks; and bank capital does not affect the profitability of Indonesian and Malaysian banks.